Kustode – et essay om skønhed og udyr i Europas erindring - Banke, Cecilie Felicia Stokholm (Slagmark - Tidsskrift for idéhistorie, 2018)
During the past two decades, memory culture surrounding the Second World War has developed from a narrow focus on “when we were at war” to the current broader focus on complex and universal issues such as human rights, reconciliation, justice, and atonement. This development has given the war and Holocaust museums a dynamic position within the current political culture of Europe. But what do we actually remember when we insist on keeping alive the memory of the Holocaust, genocide, and political mass violence: The lives which were lost during these atrocities? Or the violence that created the losses? In this essay, the author presents a series of reflections on memory culture around the Holocaust and other mass atrocities that has developed in Europe since the fall of communism.